2018
DOI: 10.1021/acs.cgd.8b00201
|View full text |Cite
|
Sign up to set email alerts
|

Particle Breakage Kinetics and Mechanisms in Attrition-Enhanced Deracemization

Abstract: In this study, we report on experiments designed to deconvolute the particle breakage kinetics and mechanism from the parallel phenomena (growth-dissolution, agglomeration) in attrition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 59 publications
(147 reference statements)
3
37
0
Order By: Relevance
“…This Kapur function analysis showed that stable cavitation bubbles mostly break via fracturing while relative more abrasion was present when transient bubbles were created. Using a similar setup to the previous study, Xiouras et al also studied quantitatively the ultrasound breakage behavior of NaClO3 particles suspended in the antisolvent hexane at a frequency of 41 kHz and 30W (absorbed electrical power) and compared the breakage behavior with that using bead grinding [120]. It was found that for the specific compound, ultrasound led to abrasion, generating many fine particles, while bead grinding caused mostly fracture of the crystals.…”
Section: 5fragmentation / Deagglomeration 251 Observations On Ultrasound Assisted Fragmentation / Deagglomerationmentioning
confidence: 94%
“…This Kapur function analysis showed that stable cavitation bubbles mostly break via fracturing while relative more abrasion was present when transient bubbles were created. Using a similar setup to the previous study, Xiouras et al also studied quantitatively the ultrasound breakage behavior of NaClO3 particles suspended in the antisolvent hexane at a frequency of 41 kHz and 30W (absorbed electrical power) and compared the breakage behavior with that using bead grinding [120]. It was found that for the specific compound, ultrasound led to abrasion, generating many fine particles, while bead grinding caused mostly fracture of the crystals.…”
Section: 5fragmentation / Deagglomeration 251 Observations On Ultrasound Assisted Fragmentation / Deagglomerationmentioning
confidence: 94%
“…In addition, recently many emerging technologies have also been developed to achieve this goal. Crystallisation of a racemic mixture is an effective approach to enrich one enantiomer by the formation of conglomerate crystals 24 , 25 or through spontaneous deracemization during crystallisation 26 , 27 . Futhermore, coherent laser light 28 and highly enantioselective enzymes 29 have been used for efficient deracemization.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous groups report the positive impact of ultrasound, including significantly reducing the induction time [18] , [19] , [20] , [21] , [22] , [23] , reducing the metastable zone width (MSZW) [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] and improving the rate of formation of new nuclei [27] , [28] . In addition, ultrasound has been shown to control final crystal properties such as the crystal size distribution [29] , [30] , [31] , [32] , [33] , [34] , [35] , crystal polymorphism [34] , [36] , [37] , [38] and crystal chirality [39] , [40] , [41] , [42] , [43] – all of which are very important to control, particularly in the pharmaceutical and food industries. Given the complexity of ultrasonic cavitation and traditional crystallisation and the various factors that impact both processes, and despite a significant body of research investigating ultrasound’s effect on the crystallisation process, the detailed mechanisms involved remain elusive.…”
Section: Introductionmentioning
confidence: 99%